Pengaruh Good Corporate Governance dan Modal Intelektual terhadap Nilai Perusahaan - Sawitri, Ni Kadek Umi; Wahyuni, Made Arie (Universitas Pendidikan Ganesha, 2021)
This study aims to determine the effect of Good Corporate Governance (managerial ownership and institutional ownership) and intellectual capital on firm value. This research is a quantitative research. The population in this study were manufacturing companies on the Indonesia Stock Exchange and the sample in this study were 52 companies with the sampling technique using purposive sampling. In this study, the data used are secondary data. The analysis used in this study is multiple linear regression analysis with the SPSS Version 20.0 program. The results in this study indicate that (1) the managerial ownership variable has a positive and significant effect on firm value, this can be seen in the results of hypothesis testing, (2) managerial ownership variables also have a positive and significant effect on firm value, (3) ) The intellectual capital variable has a positive and significant effect on firm value, the three variables in this study have positive and significant results on firm value, so it means that these three variables have a very large influence on firm value.